Folhas volantes: o cordel encantado como saber cultural e prática educativa no Nordeste na Amazônia Paraense - Castro, José Guilherme de Oliveira; de Oliveira, Elaine Ferreira; Possas, Hiran de Moura (Revista Cocar, 2019)
Flyleaf: The enchanted Cordel as KnowledgeL culture and educative practice in the northeast in the Amazon Paraense Resumo Este artigo tem como objetivo analisar a influência da literatura popular do Nordeste brasileiro, nas produções dos folhetos de cordel, na Amazônia paraense, mais precisamente, no município de Paragominas. No decorrer do estudo, será mostrada a origem do gênero, vindo das “folhas volantes” que circulavam nas terras portuguesas, a penetração no território brasileiro e a migração para as cidades nortistas. Também se pretende elencar as causas da chegada desses cantares à cidade de Paragominas, e ainda analisar as adaptações da forma poética do Nordeste aos temas locais. Serão apresentados alguns trovadores – homens e mulheres, destacando as características de suas obras. Neste ponto, serão enfatizados os gêneros e as espécies literárias cultivados por esses artistas, os recursos estilísticos, como também a adaptação da herança nordestina aos temas da Amazônia. Palavras-chave: Literatura popular. Cordel. Recurso estilístico. Abstract This article aims to analyze the influence of the popular literature of the Brazilian Northeast, in the productions of the leaflets of Cordel, in the Amazon Paraense, more precisely, in the municipality of Paragominas. During the study, it will be shown the origin of the genus, coming from the "flywheels" that circulated in the Portuguese lands, the penetration in the Brazilian territory and the migration to the northeastern cities. It is also intended to elicit the causes of the arrival of these song in the city of Paragominas, and also to analyze the adaptations of the poetic form of the northeast to local themes. Some troupters will be presented – men and women, highlighting the characteristics of their works. At this point, the genres and literary species cultivated by these artists will be emphasized, the stylistic resources, as well as the adaptation of the northeastern heritage to the themes of the Amazon. Keywords: Popular literature. String. Stylistic appeal.